2004
DOI: 10.2169/internalmedicine.43.213
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Steroid Therapy for Pacing Failure in a Patient with Chronic Myocarditis

Abstract: A 66-year-old man had a progressive increase in the pacing threshold over a one-year period, resulting from chronic myocarditis. Following steroid therapy, the pacing threshold decreased and became stabilized, and was accompanied by a decrease in the serum creatine kinase, cardiac myosin light chains and pro-collagen III peptide values, but cardiac function did not improve. Endocardial biopsy showed that there was no progression in the fibrosis. The pacing failure improved, but the cardiac function did not. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In the heart, there is evidence from experimental and human studies indicating that glucocorticoid treatment is harmful, leading to cardiomyopathy (Zecca et al. , 2001; Mitsuya et al. , 2004) characterized by an accumulation of lipid droplets, cardiomyocyte hypertrophy and dissolution of myofibrils (Clark et al.…”
Section: Influence Of Glucocorticoids On the Cardiovascular Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In the heart, there is evidence from experimental and human studies indicating that glucocorticoid treatment is harmful, leading to cardiomyopathy (Zecca et al. , 2001; Mitsuya et al. , 2004) characterized by an accumulation of lipid droplets, cardiomyocyte hypertrophy and dissolution of myofibrils (Clark et al.…”
Section: Influence Of Glucocorticoids On the Cardiovascular Systemmentioning
confidence: 99%
“…In the heart, there is evidence from experimental and human studies indicating that glucocorticoid treatment is harmful, leading to cardiomyopathy (Zecca et al, 2001;Mitsuya et al, 2004) characterized by an accumulation of lipid droplets, cardiomyocyte hypertrophy and dissolution of myofibrils (Clark et al, 1982;de Vries et al, 2002). In the adult, dexamethasone treatment can induce hypertrophy and precocious degeneration of cardiomyocytes (de Vries et al, 2002) while glucocorticoid exposure in neonates can induce myocardial hypertrophy and changes in contractile proteins (Werner et al, 1992;La Mear et al, 1997).…”
Section: Cardiovascular Remodellingmentioning
confidence: 99%
“…Epidemiological studies suggest that atherosclerosis and myocardial infarction occur in patients with long-term glucocorticoid treatment or Cushing's syndrome (33,109,187). Recent clinical reports also indicated that glucocorticoid treatment in newborn fetuses and aged patients potentially induced cardiomyopathy (113,203). Although this pathological process is not yet completely elucidated, some early morphological evaluations indicated that glucocorticoid-induced cardiomyopathy is characterized by increased accumulation of lipid droplets, cardiomyocyte hypertrophy, and dissolution of myofibrils (31,36).…”
Section: Glucocorticoids and Heart Diseasementioning
confidence: 99%
“…These actions can be correlated to the complex effects of these drugs in the healing process [16][17][18] , such as progressive decrease of the fibroblast number, thus, the collagen synthesis with consequent delay in healing. And it is also possible that, in addition to the leukocytes and fibroblasts inhibition, the corticosteroids exercise these actions through the cytokines reduction and cellular growth factors 17 .…”
Section: Major Findingsmentioning
confidence: 99%